(untitled) (Global Journal of Human-Social Science, 2011)
Nowadays the societies which are confronted with significant challenges that dealing with them have become the most important concern of the urban managers Although the managers are considered to be responsible in this regard citizens might be able to play an even better role by presenting their ideas for cities problems Tehran as a metropolis is an example of those cities on their ways to modernization facing with emerging problems and issues From 2009 a system for accumulation and surveillance of these ideas is nominated Idea Bank is implemented The Idea Bank is introduced and the impact of the framing effects on experts judgment and decision making would be analyzed in this research A sample of 202 expert members of the system is investigated Based on the obtained results idea generation resembles expenditure of money in order to buy a good or use a service and from the mental accounting point of view it creates a mental account In this research we have indicated that how the conflicts arising from framing effects in people s decision making could influence experts decision and judgment for prevention of closing the accounts containing loss therefore hazards concerning these effects should be considered as a critical factor for effectiveness of the idea bank